Implementasi policy of household waste management in South Minahasa District - Lumowa, Cristo; Lumingkewas, Lexie; Mokat, Jetty Erna Hilda (Technium Social Sciences Journal, 2021)
This study aims to describe and analyze the implementation of household waste management policies in Amurang City and the factors that hinder the implementation process. This study uses a qualitative approach by using participatory observation techniques and in-depth interviews and studying related documents. Data sources are the community, the old law, the sub-district head, and the South Minahasa Regency Environmental Service. The conclusions from this study are: the implementation of household waste management policies in Amurang City has not been fully implemented as actualized field determined through the waste management policy by the South Minahasa Regency Government. Several factors inhibit the implementation of household waste management policies in Amurang City: the coordination/ communication built by the government to the community is limited to information, while formal socialization is still very minimal, human resources, in this case, cleaning staff are still limited. Very minimal number and insufficient financial resources and standard operating procedures do not work as they should. Furthermore, there are no strict sanctions related to waste management policies in South Minahasa Regency. For this reason, the authors suggest: 1) Recommend to the Regional Government to issue further regulations related to waste management that contain strict sanctions; 2) There is a need for socialization related to waste management as a whole starting from Regency Government Officials to the community in stages; 3) It is necessary to form community social groups in communal waste management and be supported by the government and the private sector so that community participation in waste reduction and handling can work; and 4) Waste facilities and infrastructure need to be considered, the waste operational budget/financing must be added.